Comprehensive Analysis of Evolutionary Characterization and Expression for Monosaccharide Transporter Family Genes in Nelumbo nucifera - Wu, Peng; Zhang, Yongyan; Zhao, Shuping; Li, Liangjun (Frontiers in Ecology and Evolution, 2021)
Sugar transporters, an important class of transporters for sugar function, regulate many processes associated with growth, maturation, and senescence processes in plants. In this study, a total of 35 NuMSTs were identified in the Nelumbo nucifera genome and grouped by conserved domains and phylogenetic analysis. Additionally, we identified 316 MST genes in 10 other representative plants and performed a comparative analysis with Nelumbo nucifera genes, including evolutionary trajectory, gene duplication, and expression pattern. A large number of analyses across plants and algae indicated that the MST family could have originated from STP and Glct, expanding to form STP and SFP by dispersed duplication. Finally, a quantitative real-time polymerase chain reaction and cis-element analysis showed that some of them may be regulated by plant hormones (e.g., abscisic acid), biotic stress factors, and abiotic factors (e.g., drought, excessive cold, and light). We found that under the four abiotic stress conditions, only NuSTP5 expression was upregulated, generating a stress response, and ARBE and LTR were present in NuSTP5. In summary, our findings are significant for understanding and exploring the molecular evolution and mechanisms of NuMSTs in plants.